RESEARCH ON THE SOAK-ASHING PROCESSES OF STRUCTURALLY INHOMOGENEOUS LEATHER RAW MATERIAL - DANYLKOVYCH АNATOLII; ROMANIUK, OKSANA; MEREZHKO, NINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The aim of the work is to study the action of chemical reagents based on electrochemically activated water in the soaking-ashing processes of processing horse hide raw materials when forming leather material for a wide range of products. The work used horse hide weighing 13.2 kg, which was processed in halves using experimental and control technologies in a laboratory drum with an internal diameter of 3 dm and a volume of 18 dm3 at a mixing speed of the reaction system of 16–18 min–1. The technology of soaking and salting processes of horse raw materials using electrochemically activated water has been developed. The use of optimal ratios of catholyte to anolyte 5/1–3/1 at pH 8.3–7.5 and temperature 26–28 °C when soaking canned raw materials made it possible to exclude from the technology the surfactant and alkaline reagents – sodium carbonate and sodium sulfide, which are used in the control technology. At the same time, the duration of the soaking process was reduced by 2.3 times compared to the current technology. The process of salting of the semi-finished product, as well as soaking, using the experimental technology using only the catholyte, occurs more effectively with defibrillation of the collagen structure. According to the results of the study of the physicochemical properties of the semi-finished product using the experimental and control technologies of salting using the catholyte, a significant reduction in the consumption of hazardous chemical reagents is ensured with a more efficient implementation of this process. At the same time, increased uniformity of the properties of the semi-finished product was achieved along the topographic sections of the experimental technology, which indicates the production of a more structurally homogeneous semi-finished product suitable for effective subsequent technological processing.